Effects of gravity and buoyancy on spontaneous liquid-liquid imbibition in fractured porous media - Hui Cheng; Fuyong Wang (Capillarity, 2024)
Spontaneous imbibition in porous materials has received significant attention in recent decades; however, spontaneous liquid-liquid imbibition in fractures has not been well studied. Specifically, the mechanism behind the influence of gravity and buoyancy on the spontaneous imbibition of wetting phase fluid into fractured porous media remains uncertain. In this study, an analytical solution for spontaneous imbibition in fractured porous media under the influence of gravity and buoyancy is presented. The results show that imbibition velocity with buoyancy and gravity is faster than that without these forces. The effect of buoyancy and gravity on imbibition velocity increases with rising fracture aperture and length. When the fracture aperture is less than 1 μm, the relative deviation between imbibition height with and without gravity and buoyancy is about 50%. On the other hand, when the fracture aperture is greater than 1 μm, the relative deviation is proportional to the fracture aperture. The relative reduction in imbibition height over time is not obvious when the fracture aperture is the same. In the process of water-oil spontaneous imbibition, the effect of buoyancy and gravity is more pronounced at low oil-water interfacial tension. Therefore, the effect of buoyancy and gravity on spontaneous imbibition cannot be ignored under this condition. Document Type: Original article Cited as: Cheng, H., Wang, F. Effects of gravity and buoyancy on spontaneous liquid-liquid imbibition in fractured porous media. Capillarity, 2024, 10(1): 1-11. https://doi.org/10.46690/capi.2024.01.01